Interseksionalitas Perempuan Ahmadiyah: Politik Identitas dan Resistensi melalui Media - Hasan Labiqul Aqil; Adamu Abubakar Muhammad (An-Nadwah, 2024)
This research explores the intersectionality of Ahmadiyya women in Indonesia, who face layered discrimination based on their gender and religious identities. Using a case study method, this research analyzes how Ahmadiyya women use media to combat discrimination and advocate for their identity politics. Data were collected through direct observation, in-depth interviews, and analysis of audio-visual materials. Findings indicate that Ahmadiyya women face various forms of discrimination, ranging from verbal and physical violence to structural barriers, such as obtaining official state documents. They respond with both private and public forms of resistance, utilizing platforms like YouTube to voice their experiences and demand justice. Channels such as Ahmadi Talk, Islam Ramah TV, and Warta Ahmadiyah serve as crucial media for Ahmadiyya women to construct self-representation and promote peace values. This research highlights the importance of media usage in Ahmadiyya women's identity politics and resistance, as well as their contribution to advocating religious freedom and pluralism in Indonesia.